Inventory of Bamboo in Gondang District, Mojokerto Taman Regency Raden Soerjo Grand Forest - Sa’diyah, Chalimatus; Novita Kartika Indah (LenteraBio : Berkala Ilmiah Biologi, 2023)
Bamboo forests are the main habitat for animals as a place of refuge, such as in the Tahura area in the form of natural forest conservation land which aims to record animals, collect and preserve plants for educational and research needs. This research aims to inventory the diversity of bamboo species and distribution in Gondang District, Mojokerto Regency. The research used observational methods by exploring the forest to create observation tracking routes, with bamboo sample research objects in the form of roots, stems, midribs, bamboo shoots and leaves. The data is presented with identification keys, tables and descriptions of bamboo morphology as well as a map of the distribution of coordinates where bamboo was found. The inventory results showed that there were 1005 individuals in six species in four bamboo genera, namely Bambusa, Dendrocalamus, Gigantochloa and Schizostachyum. In Gumeng Village, six types of bamboo were found, namely B. vulgaris, D. asper, G. apus, G. atter, S. silicatum and S. zollingeri. In Ngembat village, three types of bamboo were found, namely D. asper, G. apus and G. atter. The distribution of bamboo is spread widely in 16 blocks with individual clumps in dense clusters in the villages of Gumeng and Ngembat.